2021
DOI: 10.1101/2021.05.05.442454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dengue virus NS1 protein conveys pro-inflammatory signals by docking onto human high-density lipoproteins

Abstract: The nonstructural NS1 protein is a virulence factor secreted by dengue virus (DENV)-infected cells. NS1 is known to alter the complement system, activate immune cells and perturb endothelial barriers. Here we show that pro-inflammatory signals are triggered by a high affinity complex formed between NS1 and human high-density lipoproteins (HDL). Electron microscopy images of the NS1-HDL complexes show spherical HDL particles with rod-shaped NS1 protrusions on their surface. These complexes are readily detectabl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 83 publications
(90 reference statements)
3
3
1
Order By: Relevance
“…This suggests that there could be a dynamic equilibrium between the HDL-bound NS1 and free NS1, regulated by the interplay between NS1 secretion and circulating HDL. Additionally, our cryoEM structures are in agreement with a recent report of a reconstituted DENV NS1:HDL complex that showed NS1 dimers anchored at the surface of HDL particles (15). .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that there could be a dynamic equilibrium between the HDL-bound NS1 and free NS1, regulated by the interplay between NS1 secretion and circulating HDL. Additionally, our cryoEM structures are in agreement with a recent report of a reconstituted DENV NS1:HDL complex that showed NS1 dimers anchored at the surface of HDL particles (15). .…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that there could be a dynamic equilibrium between the HDL-bound NS1 and free NS1, regulated by the interplay between NS1 secretion and circulating HDL. Additionally, our cryoEM structures are in agreement with a recent report of a reconstituted DENV NS1:HDL complex that showed NS1 dimers anchored at the surface of HDL particles ( 15 ).. Finally, the detection and quantification of NS1 from a ApoA1 pull-down using commercial antibodies in DENV1-infected patient serum ( 33 ) provides indirect evidence that HDL-bound NS1 complexes are also clinically relevant (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was recently shown that NS1 binds to HDL and with a lower affinity to LDL, and NS1-HDL complexes induced proinflammatory cytokine production from monocyte-derived macrophages in vitro [5]. While many early studies have suggested that secretory NS1 circulates as a hexamer, with a lipid core, more recent studies suggest that secretory NS1 circulates predominantly as a tetramer associated with HDL [11].…”
Section: Introductionmentioning
confidence: 99%
“…While many early studies have suggested that secretory NS1 circulates as a hexamer, with a lipid core, more recent studies suggest that secretory NS1 circulates predominantly as a tetramer associated with HDL [11]. During the course of the illness, the apolipoproteins that associate with NS1 have shown to change, with ApoAI and ApoB interacting with NS1 during acute illness but replaced by ApoE towards the recovery phase of illness [5]. Therefore, the lipid composition of the NS1 hexamer/tetramer or lipids that interact with NS1, could also contribute to the virulence of NS1 and potentially help explain some of the variability in previous studies [40].…”
Section: Introductionmentioning
confidence: 99%